Little-Known Operations of the Soviet Troops in Liberation of Czechoslovakia - V. B. Makovsky (Vestnik MGIMO-Universiteta)
RETRACTEDSuccessful advances of Soviet troops during the East Carpathian offensive created very favorable conditions for further operations to liberate Czechoslovakia. The breakthrough by Soviet troops of powerful natural barriers - the Eastern Carpathians with strongly fortified defensive positions created an entirely new situation on the Carpathian-Prague direction. The enemy lost an important strategic milestone, a cover of Czechoslovakia from the east. There were favorable conditions for the further deployment of the Red Army offensive deep into Czechoslovakia and access to the southern border of Germany. During this operation the right wing of the 2nd and 4th Ukrainian Fronts entered the territory of Czechoslovakia and by the end of 1944 liberated a large part of South and South-East Slovakia, surrounded by the large enemy grouping. During the offensive they managed to destroy about four divisions of the enemy, and capture more than 68 thousand troops. In March - April 1945 as a result of the fighting of the 2nd and 4th Ukrainian fronts and friendly Czechoslovak and Romanian forces large groups of the Wehrmacht were defeated in the Western Carpathians. Slovakia and Moravia were completely liberated, including such major administrative and industrial centers such as Prague, Brno and Moravian Ostrava. Within six weeks the troops advanced on both fronts more than 150-350 km, reaching the southern regions of Germany and central regions of Czechoslovakia, occupying a favorable position for an attack on Prague and the final defeat of the Wehrmacht.